1991
DOI: 10.1002/cem.1180050407
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pattern recognition descriptors for chemical acoustic emission analysis

Abstract: SUMMARYFeatures used to characterize acoustic emission signals from chemical systems are evaluated with regard to their potential for pattern recognition. Eight chemical systems involving phase transitions, hydration, dissolution and effervescence are employed and treated as separate signal classes. These are compared pairwise and the discriminatory capabilities of about 50 features are investigated by computing Fisher weights. Time domain and frequency domain descriptors are examined. Correlations among the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Figure 1 shows an AE burst, accompanying the T * (a), and the corresponding fast Fourier transform (FFT) spectrum from PST-8 (b). Both the AE burst and the FFT spectrum look similar as those previously reported [27]. The AE burst attenuates slowly and monotonically during of about 0.082 ms.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Figure 1 shows an AE burst, accompanying the T * (a), and the corresponding fast Fourier transform (FFT) spectrum from PST-8 (b). Both the AE burst and the FFT spectrum look similar as those previously reported [27]. The AE burst attenuates slowly and monotonically during of about 0.082 ms.…”
supporting
confidence: 84%
“…It is clear, while AE is able to detect both T * and T * tw [22,26], that the mentioned above differences are expected to appear in their frequency spectrum of AE. Indeed, previously an analysis of the frequency spectrum of the waveform of AE bursts indicates the matching between sizes of entities of the different chemical systems, undergoing the phase transitions, hydration, dissolution etc., and the corresponding spectrum of AE bursts from them [27]. Moreover, it was observed that the maxima of the frequency spectrum of AE bursts shift to lower frequencies when increasing the sizes of the entities, i.e.…”
mentioning
confidence: 98%